Drug-Induced Extrapyramidal Symptoms Scale of the Norwegian version: inter-rater and test–retest reliability. (17th November 2019) - Weidle, Bernhard; Chaulagain, Ashmita; Stensen, Kenneth; Aleksic, Branko; Skokauskas, Norbert; Inada, Toshiya
Abstract: Background: The Drug-Induced Extrapyramidal Symptoms Scale (DIEPSS) is a multidimensional rating scale designed for the fast, easy and reliable assessment of extrapyramidal symptoms (EPSs) induced by antipsychotics. Aim: The aim of this study was to validate the level of inter-rater and test–retest reliability of the Norwegian translation of this scale. Methods: A total of 125 video clips showing a variety of or no signs of EPSs were used in the present study. The participants recorded were Japanese psychiatric patients receiving first- and/or second-generation antipsychotics. A total of 103 patients (47 males and 56 females), diagnosed with schizophrenia ( n  = 68) or mood disorders ( n  = 35) appeared in the video clips. Their mean age was 48.7 ± 16.3 years (range 18–80) at the time of video recording. Inter-rater agreement was assessed with five raters and test–retest reliability with three. Results: Inter-rater reliability analyses showed interclass correlation coefficients (ICCs) ranging from 0.74 to 0.93 for each individual item. Test–retest reliability analysed independently for each rater ranged from 0.71 to 0.96. Conclusions: Inter-rater and test–retest agreement exhibited satisfactory ICC levels above 0.70. The Norwegian version of the DIEPSS is a reliable instrument for the assessment of drug-induced EPSs.